2008
DOI: 10.1080/08958370802207292
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Effects of Cadmium on Olfactory System in Mice

Abstract: The inhalation of certain metals can result in olfactory epithelial injury, an altered sense of smell, and direct delivery of the metal from the olfactory epithelium to the olfactory bulbs and other parts of the central nervous system. The purpose of this study was to examine whether mice given an intranasal instillation of cadmium would develop altered olfactory function and to assess whether cadmium may be transported directly from the olfactory epithelium to the central nervous system. To evaluate cadmium's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Our findings were consistent with previous animal studies and population studies in occupational settings. In a mouse study, Bondier et al [35] found that the olfactory route was likely to be one way by which cadmium can reach the brain. Sulkowski et al [36] found significant associations between olfactory dysfunction and blood and urinary cadmium levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with previous animal studies and population studies in occupational settings. In a mouse study, Bondier et al [35] found that the olfactory route was likely to be one way by which cadmium can reach the brain. Sulkowski et al [36] found significant associations between olfactory dysfunction and blood and urinary cadmium levels.…”
Section: Discussionmentioning
confidence: 99%
“…Metals can also be mentioned. Olfactory uptake has been demonstrated for mercury , manganese , cobalt , zinc , thallium and cadmium in rats and mice.…”
Section: Introductionmentioning
confidence: 99%
“…In another animal experiment, administration of 400 μg of CdCl 2 to mice by intranasal instillation resulted in partial damage to the olfactory epithelium, reversible loss of olfactory discrimination, and specific cadmium deposition in the olfactory bulb but not in other parts of the central nervous system [39]. Czarnecki et al [40] also observed anosmia in a behavioural test following intranasal instillation of a cadmium chloride solution in mice.…”
Section: Industrial Chemicals With a Potential Impact Upon Olfactionmentioning
confidence: 99%
“…Over 1000 axons of olfactory receptor neurons with the same receptor type project onto the dendrites of a single mitral cell [138]. Cadmium and manganese can be detected in the bulbus olfactorius of animals (see above, [38, 39, 63, 68, 72]) and in humans: Baader (1952) was able to determine atrophy of the nasal mucous membrane and an intensive yellow colouring of the olfactory bulb following the autopsy of an affected worker exposed to cadmium, which led him to suspect that cadmium reached the brain via the olfactory pathway [146]. After MRT research on non-human primates exposed to aerosolised manganese sulfate (particle diameter: 1.04–2.12 μm) had already demonstrated transport of manganese via the olfactory pathway and accumulation of manganese in the olfactory bulb [147], increased deposition of manganese in the olfactory bulb was also detected on 7 welders by means of functional magnetic resonance tomography [63].…”
Section: Mechanism Of Olfactory Dysfunctionmentioning
confidence: 99%